Stakeholder relationship management as a tool for municipal public value generation: a case study of five municipalities in the Western Cape - Haarhoff, Kosie Jacobus (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.